2011
DOI: 10.1097/hco.0b013e32834b7faf
|View full text |Cite
|
Sign up to set email alerts
|

Why are women more likely than men to develop heart failure with preserved ejection fraction?

Abstract: The prevalence of HFpEF is increasing and women outnumber men by a 2 : 1 ratio. Recent data have identified striking parallels between structure-function alterations observed in HFpEF and sex differences in cardiovascular function across the adult lifespan. These data suggest that sex-specific maladaptations to hypertensive aging in women may underlie greater risk of HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 70 publications
9
142
0
2
Order By: Relevance
“…92, 93 In addition, the ability to tolerate volume loading without excessive increase in LVFP decreases in older women. 94 Given these observations, together with the foregoing findings, therapies targeting age-related LV diastolic stiffening would appear to hold promise to help improve exercise capacity and outcomes in HFpEF.…”
Section: Exercise Reserve Hfpef and Normal Agingmentioning
confidence: 99%
“…92, 93 In addition, the ability to tolerate volume loading without excessive increase in LVFP decreases in older women. 94 Given these observations, together with the foregoing findings, therapies targeting age-related LV diastolic stiffening would appear to hold promise to help improve exercise capacity and outcomes in HFpEF.…”
Section: Exercise Reserve Hfpef and Normal Agingmentioning
confidence: 99%
“…Levy et al [18] observed that risk for HF in hypertensive when compared to normotensive, was twice as high in men and three times higher in women [10,12]. Framingham Heart Study also reported that diabetic women, even at ages 35 to 64, were twice as likely to develop HF as diabetic men of the same age.…”
Section: Risk Factors and Aetiologymentioning
confidence: 87%
“…The Euro Heart Survey of Stable Angina observed that inadequate and casual management of IHD in women in the past may be the cause for a higher incidence and early prevalence of HF in elderly women after MI [18]. Valvular heart disease particularly obstructive pathology (aortic stenosis/mitral stenosis) is another important cause of HF in women, than in men.…”
Section: Risk Factors and Aetiologymentioning
confidence: 99%
“…They have more pronounced concentric ventricular remodelling and less dilation in response to hypertension. 15 Therefore they are more likely to develop cardiac failure. 15 Whether this translates to greater perioperative risk among women needs to be studied.…”
Section: Discussionmentioning
confidence: 99%